Everyday culture is a phenomenon of the Kazakh people: (Journal of Philosophy Culture and Political Science, 2025)
The research topic is devoted to the cultural traditions of Kazakhstan, including the influence of nomadic culture on everyday life, as well as regional features and their significance in modern society. Understanding traditional cultural elements in the context of globalization and social transformations helps to preserve national identity and assess their role in modern society. The purpose of the work is to study the relationship between traditional and modern elements of Kazakh culture, analyze their significance for the social structure and national identity.The main directions are the features of traditions such as hospitality, food, language and social norms in different regions of Kazakhstan, as well as the impact of the Soviet period on these traditions. The research methodology is based on the study of cultural and social analysis methods, as well as regional features and traditional practices. The main results of the study are aimed at identifying the deep connection between nomadic traditions and modern Kazakh culture, as well as showing how regional differences affect cultural practices and norms. The contribution of this work allows us to deeply understand the impact of nomadic culture on modern Kazakh society and to study regional cultural features. The practical significance of the work lies in the application of the results obtained to develop social and cultural initiatives to strengthen national identity and preserve cultural traditions.Key words: nomadic culture, traditions, Kazakhstan, regional differences, national identity.